Unfettering poetry : fancy in British Romanticism - Robinson, Jeffrey Cane, 1943- (Palgrave Macmillan, 2006)
In Unfettering Poetry: The Fancy in British Romanticism, Jeffrey C. Robinson argues that politically progressive Romantic poets write with a politically progressive or radical poetics, coded during the Romantic Period as 'the Fancy.' Traditional readings of Romantic poetics that emphasize the drama of the speaker or lyric subject reveal a pervasive 'fanciphobia, ' or fear of the Fancy's inclination for a poetry of inclusiveness, expansiveness, and visionary transformation of the object or 'the world, ' and of an experimentation with and unfettering of poetic form and content. In fact, Robinson locates a poetry of the Fancy as the bedrock of Romantic poetic intention (having resonances in the experimental poetries of the late-nineteenth and twentieth centuries), with extended readings of the relatively unexplored poetry of Robinson, Hunt, Reynolds, Clare, and Hemans, as well as a radical rethinking of the familiar poetry of Wordsworth and Keats.